Evaluating Career Development in School-Based Programs: Performance Assessments - Hutchinson, Nancy L. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper makes a case for using performance assessments in career development interventions conducted in the classroom. Examples are drawn from Pathways, a recently developed Canadian program for career development. Limitations of performance assessment are discussed, followed by recommendations for practice and research.